Mengurangi Cacat Produk Dengan Implementasi PDCA : (Studi Kasus Perusahaan Pt Xyz) - Revica Tauriza Alfiane; Rusindiyanto (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
The emergence of the development of an industry is one of human efforts to survive. One of them is PT XYZ. Where PT XYZ is required to maintain its quality by reducing the number of defects in its production process. Reducing defects is very important to do. One of the appropriate methods for reducing empty pouches is the PDCA (Plan, DO, Check, and Action) method. This method is very effective in solving existing problems at PT XYZ. The results of the analysis that have been carried out have not had an optimal impact on the presentation of empty pouch defects where the company's standard percentage is 2%. In the data before repairs were carried out, the percentage of empty pouch defects had an average of 3.6%, but when repairs were carried out the average percentage of defects was still high, namely 3.5%. in the evaluation stage of the training period. Where further research can be carried out with the advice that can be given is being able to standardize each production process, and being able to be consistent in carrying out the improvements that have been made.